Asymptotic safety in an interacting system of gravity and scalar matter - Donà, Pietro; Eichhorn, Astrid (Physical review, 2016)
Asymptotic safety is an attractive scenario for the dynamics of quantum spacetime. Here, we work from a phenomenologically motivated point of view and emphasize that a viable dynamics for quantum gravity in our Universe must account for the existence of matter. In particular, we explore the scale dependence of a scalar matter-gravity vertex, and investigate whether an interacting fixed point exists for the so-defined Newton coupling. We find a viable fixed point in the pure-gravity system, disregarding scalar quantum fluctuations. We explore its extensions to the case with dynamical scalars, and find indications of asymptotic safety in the matter-gravity system. We moreover examine the anomalous dimensions for different components of the metric fluctuations, and find significant differences between the transverse traceless and scalar component.